Analysis of climate impacts in Costa Rica, Central America, from local historical information sources - Alfaro Martínez, Eric J. (2012)
Central America and Mexico is a region that account for many World Heritage Sites. Among the climate hazards that affects this rich world heritage place of the world are the boreal winter cold fronts intrusions, also known as cold outbreaks or more locally as “Nortes”. During summer-autumn the region is affected by easterly waves and by the activity of two tropical cyclone regions, the Atlantic-Caribbean and the Eastern Tropical Pacific. For the study of regional impacts caused by these hazards are generally used public data bases like HURDAT or EMDAT, but these data bases have two major concerns for local impact studies. First, the methodologies used and the centers in charge to quantify them are sometimes different trough the history. For example, besides the satellite technologies use, the study of tropical cyclones in the Eastern Tropical Pacific, was in charge by centers located in San Francisco & Redwood City-California and finally in Coral Gables-Florida (National Hurricane Center until today) during the 1970-1980 decades. Second, some events are not consider relevant for regional or basin scale, but are very important for local purposes. An example of this was the low pressure system in May 2010 located in front of the Costa Rican pacific coast. These system developed later in Tropical Storm Agatha, but its major impacts in Costa Rica were associated with the first cyclone stages, e.g. low pressure and tropical depression. For the reasons mentioned above, this study review local information sources like national newspapers and bulletins produced by the National Weather Service, to account for relevant climate events and their associated impacts in Costa Rica. Cold fronts, easterly waves and tropical cyclones were considered as study objects from 1977 to 2011. It is state that this kind of study is very important to complement regional data bases and to avoid underestimation in the event-impact accounts. Impacts associated with cold fronts (tropical cyclones) were located mainly in the Costa Rican Caribbean (Pacific) slope while those associated with easterly waves have a more even spatial distribution trough the country. Finally, because of their nature, it is also important to develop these kind of works within a multidisciplinary team, that include researchers from climatology, history and geography fields.